Advances in Sustainable and Digitalized Factories: Manufacturing, Measuring Technologies and Systems - Calvo, Roque; Yagüe-Fabra, José A.; Tosello, Guido (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The book is the reprint of the Special Issue 'Advances in Sustainable and Digitalized Factories: Manufacturing, Measuring Technologies and Systems' published in the journal Applied Science (MDPI). It contains 17 articles, including 1 Editorial, 14 Research Papers, and 2 Reviews.